Mediation vs. force: thoughts on female agency in Apollonius Rhodius' Argonautica - Anatole Mori (Aitia, 2012)
This paper suggests that the cultural influence of the Ptolemaic queen likely contributed to the Hellenistic formulation of a new female “voice” even in male-authored Alexandrian poetry. Self-control, cooperation, and other “Argonautic virtues” are thus displayed both by female and male authority figures. In Hera’s case, her intercession on behalf of favorites recalls the agency of her Homeric counterpart, but with the marginalization of Zeus, Hera’s role as (maternal) intercessor is not only placed in higher relief but also celebrated. Moreover, Hera’s exercise of authority through a mediated chain of command contrasts favorably with the self-reliant, forceful power of Medea, Heracles, and other heroic figures.